(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
The human body develops on the basis of DNA, which contains genetic information. Each person’s genetic material contains millions of genes, which work inextricably linked to each other. Hereditary diseases mainly occur as a result of genetic mutations, chromosomal abnormalities, or gene malfunction. These diseases are inherited, that is, they are transmitted from parents to generations, or develop as a result of the negative impact of environmental factors on genetic material. The prevalence of hereditary diseases in the world is very diverse, and they have a serious impact on human health. While some hereditary diseases, such as Down syndrome or hemophilia, are widespread, other rare diseases are often ignored by the population. The study of the origin of hereditary diseases is one of the main directions of modern medicine and genetics. Within this topic, genetic diagnostics, gene therapy, methods of prevention and treatment are developing significantly. This article provides more detailed information about the causes, development mechanisms and their significance of hereditary diseases.